Pills and starships - Millet, Lydia, 1968- (New York, NY : Black Sheep, 2014)
Seventeen-year-old Nat and her hacker brother Sam have come to the Big Island of Hawaii to prepare for their parents' final week in a dystopic future brought on by global warming.
Young Adult
Young Adult
Keywords: Brothers and sisters -- Juvenile fiction; Parents -- Death -- Juvenile fiction; Brothers and sisters -- Fiction; Dystopias; Parents -- Death -- Fiction; Dystopias; Parents -- Death -- Fiction; Siblings -- Fiction; Hawaii Island (Hawaii) -- Juvenile fiction; Hawaii Island (Hawaii) -- Fiction; Hawaii Island (Hawaii) -- Fiction; Dystopias